Soil and Root Responses in Hazelnut Rhizosphere to Inoculate Rhizobacteria Immobilized via JetCutter Technology - Solange V. Benítez; Rocío Carrasco; Antonio Roldán; Fuensanta Caravaca; Manuel Campoy; Joaquín Cofré; José Ortiz; Juan D. Giraldo; Mauricio Schoebitz (Horticulturae, 2025)
Plant growth-promoting rhizobacteria (PGPR) have significant potential for enhancing soil quality and plant growth; however, their agricultural application is limited by challenges such as immobilization and desiccation vulnerability. Background: This study addressed PGPR solid formulation by applying JetCutter-assisted immobilization technology to PGPR strains isolated from the rhizosphere of hazelnut (Corylus avellana). Methods: Four immobilized PGPR strains were evaluated under controlled greenhouse conditions: Serratia proteamaculans, Pseudomonas mohnii, Pseudomonas baetica, and Bacillus safensis. Their effects on root development, gas exchange parameters, dissolved organic carbon (DOC), and soil enzymatic activities (phosphatase, urease, protease, and β-glucosidase) were assessed. Principal component analysis (PCA) was used to identify the top-performing strain. Results: Treatment with encapsulated bacteria resulted in a 27% increase in DOC compared to controls (p < 0.05), while phosphatase and urease activities increased by 35% and 28%, respectively. Root length and volume improved by 18% and 22%, respectively, with PCA identifying P. baetica as the most effective strain. Conclusions: Immobilized Gram-negative PGPR strains enhanced root development and soil biochemical activity in hazelnuts, whereas B. safensis enhanced photosynthesis but had minimal impact on soil properties. These results highlight functional differences and support the use of PGPR immobilization to promote early plant establishment.